Cannabinoids for control of chemotherapy induced nausea and vomiting: quantitative systematic review - Tramèr, M; Carroll, D; Campbell, F; Reynolds, D; Moore, R; McQuay, H (BMJ Publishing Group, 2001)
Objective: To quantify the antiemetic efficacy and adverse effects of cannabis used for sickness induced chemotherapy. Design: Systematic review. Data sources: Systematic search (Medline, Embase, Cochrane library, bibliographies), any language, to August 2000. Studies: 30 randomised comparisons of cannabis with placebo or antiemetics from which dichotomous data on efficacy and harm were available (1366 patients). Oral nabilone, oral dronabinol (tetrahydrocannabinol), and intramuscular levonantradol were tested. No cannabis was smoked. Follow up lasted 24 hours. Results: Cannabinoids were more effective antiemetics than prochlorperazine, metoclopramide, chlorpromazine, thiethylperazine, haloperidol, domperidone, or alizapride: relative risk 1.38 (95% confidence interval 1.18 to 1.62), number needed to treat 6 for complete control of nausea; 1.28 (1.08 to 1.51), NNT 8 for complete control of vomiting. Cannabinoids were not more effective in patients receiving very low or very high emetogenic chemotherapy. In crossover trials, patients preferred cannabinoids for future chemotherapy cycles: 2.39 (2.05 to 2.78), NNT 3. Some potentially beneficial side effects occurred more often with cannabinoids: "high" 10.6 (6.86 to 16.5), NNT 3; sedation or drowsiness 1.66 (1.46 to 1.89); euphoria 12.5 (3.00 to 52.1), NNT 7. Harmful side effects also occurred more often with cannabinoids: dizziness 2.97 (2.31-3.83), NNT 3; dysphoria or depression 8.06 (3.38-19.2), NNT 8; hallucinations 6.10 (2.41-15.4), NNT 17; paranoia 8.58 (6.38 to 11.5), NNT 20; and arterial hypotension 2. 23 (1.75 to 2.83), NNT 7. Patients given cannabinoids were more likely to withdraw due to side effects 4.67 (3.07 to 7.09), NNT 11. Conclusions: In selected patients, the cannabinoids tested in these trials may be useful as mood enhancing adjuvants for controlling chemotherapy related sickness. Potentially serious adverse effects, even when taken short term orally or intramuscularly, are likely to limit their widespread use.